Exploring Contemporary Perspectives in Organizational Behavior Research - Prasetya, Eka (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores contemporary perspectives on organizational behavior, focusing on leadership, organizational culture, employee motivation, and diversity and inclusion. By examining these elements, the research provides a comprehensive understanding of their impact on organizational effectiveness. Research Design and Methodology: A qualitative literature review was conducted to synthesize existing research on organizational behavior. Scholarly articles, books, and reports were reviewed, focusing on theoretical frameworks and empirical studies on leadership styles, cultural dynamics, motivational factors, and inclusive practices. Findings and Discussion: The review highlights the significance of transformational leadership in enhancing employee engagement and performance. Influential organizational culture, characterized by shared values and norms, is critical in shaping behavior and promoting innovation. Employee motivation, influenced by intrinsic and extrinsic factors, is crucial for productivity and satisfaction. Diversity and inclusion contribute to creativity and problem-solving, improving organizational outcomes. However, challenges such as unconscious bias and systemic barriers need to be addressed to foster genuinely inclusive environments. Implications: Integrating insights from organizational behavior research into practice can enhance leadership effectiveness, cultural alignment, and employee motivation. Organizations should invest in leadership development, promote a positive and adaptive culture, and implement diversity and inclusion initiatives. Future research should focus on longitudinal studies and interdisciplinary approaches to address emerging trends and complexities in organizational behavior.